Disposal Methods of Expired and Unused Medications among the General Public in Al-Bayda City - Taher I. Mahmod Shailabi; Zuhir S. Mussa Akrim (مجلة المختار للعلوم, 2021)
Medication disposal is a hot topic in pharmacy today, and it is rapidly gaining the attention of more and more professionals and consumers alike. Improper disposal of expired or unused medications has been reported to create serious consequences on healthcare and the environment. This study was performed to determine how residents of Al-Bayda, in the north-eastern region of Libya, dispose of their unused and expired medications and discuss the possible impact of improper medication disposal on humans, animals, and the environment. Data was collected over six months within Al-Bayda city as people were approached randomly and invited to participate by filling out a questionnaire to examine their expired medicine disposal habits. With responses from 925 participants, the survey found that 77.3 % disposed of medicines with household waste, 6.9 % flushed medicines down the sink or toilet, 4 % gave them to relatives or friends, 2.8 % returned medicines to the pharmacy, and 9 % do not know. Campaigns run by health care professionals, mainly pharmacists as they have a potential role to raise public awareness regarding appropriate ways to dispose of unused medicines, will promote appropriate disposal practices.